(untitled) (Dermatology Reports, 2020)
Extramammary Paget Disease (EMPD) is an often-misdiagnosed rare disorder, whose cause remains unknown. Diagnosis is confirmed by skin biopsy. Primary treatment for EMPD is surgery. Recurrence is common in the first two years and prognosis is good if the disease is localized and there is no underlying associated cancer. Patients with invasive and metastatic EMPD are uncommon and exhibit a poor prognosis, even when there is good response to a first chemotherapy line. Multiple chemotherapeutic regimens, with varying levels of success, have been attempted, but standard of care is not established. The central nervous system seems to be a common metastatic site with better survival than visceral metastasis.We report a case of metastatic EMPD that addresses the difficulties associated with the treatment of this rare disease, that has no current guidelines.